Crop insurance's impact on commercial bank loan volumes: Theory and evidence - Ifft, Jennifer; Kuethe, Todd H.; Lyons, Gregory; Schultz, Alexander; Zhu, John Y. (Applied economic perspectives and policy, 2024)
Crop insurance protects lenders by increasing the likelihood of loan repayment when revenue declines. We develop a theoretical mode that explains the role of crop insurance in agricultural lending and how impacts may be different for lenders that are not specialized in agricultural lending. We then test whether the total volume of production credit extended by commercial banks at the county level increases in response to crop insurance availability and whether the level of the response is related to bank specialization in agriculture. We use a novel difference‐in‐differences strategy based on some counties having a higher share of agricultural production that was not covered by Federal crop insurance in the 1990s. Crop insurance has a robust relationship with increased loan volumes during this period, especially in counties with fewer banks specialized in agriculture.